A arte de contar histórias e as suas: análise de uma proposta pedagógica - Harich, Regiane Ferreira Martins (2021)
The present research had the general objective of investigating whether storytelling contributes to the learning process of Early Childhood students, in the city of Santo André / SP. The specific objectives are: i) to identify the meanings constructed, by the teachers, in the pedagogical spaces to the storytelling; ii) analyze how teachers developed the storytelling process; iii) investigate the elements necessary for the moment of storytelling; iv) observe and listen to students and teachers before and after moments of storytelling. The question that guided this work was: to what extent does storytelling contribute to arouse interest in listening to stories? We start from the hypothesis that other forms of language also provide learning, promoting practices capable of establishing a greater connection with the teaching object, leading teachers to reflect on their actions relevant to their age group. The research universe was a public school, located in ABC Paulista, in the city of Santo André (SP). The subjects were two educators who work with the groups of 4 and 5 years respectively and the students. The methodology used was of a qualitative nature, the data collection instrument occurred through semi-structured interviews and observation. The theoretical framework was based on the work of researchers from childhood and storytelling, among them: Maria Cristina Rizzoli and Walter Benjamin. The results showed that the act of storytelling marked the pedagogical path of teachers and students who recognize the importance of projecting these actions in other situations. Based on that, recurring meetings of pedagogical actions were proposed.